2006
DOI: 10.1038/nm1385
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal delivery of the cytoplasmic domain of CTLA-4 using a novel protein transduction domain prevents allergic inflammation

Abstract: CTLA-4 is a negative regulator of T-cell activation, and its inhibitory effects can be accomplished either by competition with CD28 or by transmitting negative signals through its intracellular domain. To utilize the cytoplasmic domain of CTLA-4 to suppress allergic inflammation, we fused it to a novel protein-transduction domain in the human transcriptional factor Hph-1. Transduction efficiency was verified in vitro and in vivo after ocular, intranasal and intradermal administration. After transduction into T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 30 publications
0
109
0
Order By: Relevance
“…In our previous work, we identified a novel human-originated CPP, Hph-1, and showed that Hph-1-ctCTLA-4 recombinant protein inhibited T cell receptor signaling and demonstrated an inhibitory effect on allergic airway inflammation and autoimmune arthritis in animal models (Choi et al, 2006;. LPIN-CPP is newly identified in this study and has nine amino acids, which is shorter than either TAT-or Hph-1-CPP.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In our previous work, we identified a novel human-originated CPP, Hph-1, and showed that Hph-1-ctCTLA-4 recombinant protein inhibited T cell receptor signaling and demonstrated an inhibitory effect on allergic airway inflammation and autoimmune arthritis in animal models (Choi et al, 2006;. LPIN-CPP is newly identified in this study and has nine amino acids, which is shorter than either TAT-or Hph-1-CPP.…”
Section: Discussionmentioning
confidence: 71%
“…Although there has been remarkable transduction efficiency and good therapeutic effects noted for cargo molecules in vitro, in vivo application has been much more limited because of toxicity, immunogenicity, and low delivery efficiency. Recently, human-derived CPPs such as Hph-1 (Choi et al, 2006), Sim-2 (Choi et al, 2012), lactoferrin (Duchardt et al, 2009), andvectocell (De Coupade et al, 2005) were identified, however their delivery efficiencies are typically lower than that of TAT and still, in vivo delivery efficiency was not sufficient. Therefore, the development of novel humanoriginated CPPs with a higher transduction efficiency is still required.…”
Section: Introductionmentioning
confidence: 99%
“…Combinations of PPAR and RXR agonists may produce synergistic effects with reduced side effects . Administration of cell-permeable recombinant proteins may prove to be a promising approach to increasing PPAR activity in cells with minimal chemical toxicity (Choi et al, 2006;. Recent studies suggest that PPARα, PPARβ/δ, and PPARγ play important roles in T-cell survival, activation, and differentiation into Th1 or Th17 cells, implying their therapeutic potential as drug targets for treating autoimmune diseases or graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The airspace enragement of the lung was measured using a digitized image tool [17]. The pulmonary inflammation index was graded as previously described [18].…”
Section: Uplc-esi-ms Analysismentioning
confidence: 99%